Ischemic Stroke in Adults With Congenital Heart Disease: A Population‐Based Cohort Study. Issue 15 (6th August 2019) - Pedersen, Mette Glavind Bülow; Olsen, Morten S.; Schmidt, Morten; Johnsen, Søren P.; Learn, Christopher; Laursen, Henning B.; Madsen, Nicolas L.
Abstract : Background: Congenital heart disease (CHD) is associated with risk factors for ischemic stroke including cardiac arrhythmias and heart failure. However, few long‐term follow‐up data exist on ischemic stroke risk and associated mortality in adults with CHD. Methods and Results: Using Danish nationwide registries, we identified individuals aged ≥18 years diagnosed with CHD, at any age, from 1963 to 2017 and a sex and birth year‐matched (1:10) general population comparison cohort. We computed risks, as well as sex and birth year‐adjusted hazard ratios (aHRs) for ischemic stroke and 30‐day post‐stroke mortality in CHD adults compared with the general population. Analyses were stratified according to age <60 years (young) and ≥60 years (older). We identified 16 836 adults with CHD. The risk of ischemic stroke at age 60 years was 7.4% in the CHD cohort and 2.9% in the general population cohort. The adjusted hazard ratios for ischemic stroke compared with the general population was 3.8 (95% CI: 3.3–4.3) in young CHD adults and 1.6 (95% CI: 1.4–1.9) in older CHD adults. The adjusted hazard ratios for post‐stroke mortality compared with the general population was 2.3 (95% CI: 1.2–4.4) in young CHD adults and 1.3 (95% CI: 0.9–1.9) in older CHD adults. Conclusions: Both younger and older CHD adults have an increased risk of ischemic stroke and by 60 years of age 7.4% of CHD adults will have had an ischemic stroke. Post‐stroke mortality was also increased in CHD adults compared with the general population.